HYGIENIC APPRECIATION OF THE OCCUPATIONAL CONDITIONS AND THE INCIDENCE OF THE HEARING ORGAN IN THE COAL INDUSTRY WORKERS - Светлана Наильевна Раудина; Виктор Андреевич Семенихин; Сергей Николаевич Филимонов (Медицина в Кузбассе, 2020)
The subjects of the study (observation) are the Kuzbass coal industry workers with occupational sensorineural hearing loss (exposed to the noise). Aim of the study – evaluation of the hygienic characteristics of noise exposure and detection of the hearing damage in workers of the Kuzbass coal industry, depending on themethod of coal mining. Examination methods. The analysis of the incidence of sensorineural hearing lossand assessment of working conditions based on the data of sanitary and hygienic characteristics in the main professions exposed to the noise, with differentmethods of coal mining. Main results. Afteranalyzing of the data during10 years (from 2008 to 2017) amongpatients with newly identified occupational diseases, we can note a gradualdecrease in the overall incidence. At the same time the occupational sensorineural hearing lossas a percentage compared to the other diseases is not reduced. The hygienic characteristics of working conditions depend on the method ofcoal mining. In the open-cut mining there was the excess noiseup to 12 dBA in the mainprofessions, which corresponds to the 3.1 classof the working conditions, and in the underground method this value was up to 16 dBA in the most professions, it is 3.2 class, and in the rare cases it exceeded 25 dBA, which corresponds to 3.3 class. Domain of usage: occupational medicine, occupational pathology. Conclusions. In the open-cut mining the noise is within the limits of themaximum permissible level or it slightly exceeds the maximum permissible level. However, underground coal mining has ahigher noise levelexcess. The factorscomplex combined with noise leads to the more evident progression of the hearing loss. The continuing sanitary and hygienic situation in the workplace in the coalindustry of the Kuzbass enterprises involuntarily confirms the further growth of the occupational sensorineural hearing loss and the aggravation of the generalsomatic pathology.